Mobilizing Risk: Explaining Policy Transfer in Food and Occupational Safety Regulation in the UK. (February 2015) - Demeritt, David; Rothstein, Henry; Beaussier, Anne-Laure; Howard, Michael
Using comparative methods of policy analysis, this paper explores the institutional factors shaping the transfer and adaptation of risk-based approaches to regulation within and between the regimes for occupational health and safety (OHS) and food safety in the UK. Over the past two decades successive governments have enthusiastically promoted risk as a key concept for regulatory reform and 'better regulation'. Rather than trying to prevent all possible harms, 'risk-based' approaches promise to make regulation more proportionate and effective by using various risk-based metrics and policy instruments to focus regulatory standard-setting and enforcement activity on the highest priority risks, as determined through formal assessments of their probability and consequences. But despite facing similar external pressures and sharing many historical and structural features as OHS, food safety regulation has proven much less receptive to risk-based reforms of its organizing principles and practices. To explain that anomaly, we consider a range of explanations highlighted in the policy transfer and mobilities literatures. We find that coercive drivers for the adoption of risk, in the form of top-down political pressure for deregulation or hard EU mandates, are much less influential than voluntary ones, which reflect both normative (ie, shared commitments to proportionality, resource prioritization, and blame deflection) and mimetic (ie, imitation of private sector corporate governance models) isomorphism. We conclude with wider reflections about the significance of our cases for policy transfer and mobilities research and for the limits to risk as a universal principle for organizing, and accounting for, governance activity.